Stakeholder Salience in a Multistakeholder Initiative of the National Forestry Council of Indonesia - Muttaqin, Tatag; Soraya, Emma; Dharmawan, Budi; Maryudi, Ahmad (Institut Pertanian Bogor (IPB University), 2023)
This study analyzes the roles and positions of stakeholders in decision-making processes within the National Forestry Council (Dewan Kehutanan Nasional, DKN), a forest-related multistakeholder platform in Indonesia. It considers stakeholders’ power, legitimacy, and urgency. The research employed a qualitative case study, centered around in-depth interviews with 27 key informants with diverse backgrounds involved in the DKN. The study found that despite being designed to facilitate democratic and inclusive decision-making, the engagement of stakeholders in the DKN is heavily dominated by powerful government actors. Several stakeholder groups, such as NGOs and academics, may actively participate in decision-making processes, but they do not meaningfully influence and capacity to determine the organizational policy directions. This is related to an imbalance in the distribution of power among stakeholders in DKN. Even though this organization promotes the principle of inclusivity, the reality is that the presence and influence of the government are still the dominant factors in determining policy directions. This study confirms the importance of the stakeholder salience analysis approach in the context of multistakeholder initiative organizations such as the DKN, which allows recognition of power dynamics and domination among stakeholders within the DKN so that decisions made truly reflect the common interests of all parties involved.